The Mesolithic–Neolithic Transition in the Channel Islands: Maritime and Terrestrial Perspectives. Issue 1 (February 2017) - Garrow, Duncan; Sturt, Fraser
Summary: This paper investigates the Mesolithic–Neolithic transition in the Channel Islands. It presents a new synthesis of all known evidence from the islands c.5000–4300 bc, including several new excavations as well as find‐spot sites that have not previously been collated. It also summarizes – in English – a large body of contemporary material from north‐west France. The paper presents a new high‐resolution sea‐level model for the region, shedding light on the formation of the Channel Islands from 9000–4000 bc . Through comparison with contemporary sites in mainland France, an argument is made suggesting that incoming migrants from the mainland and the small indigenous population of the islands were both involved in the transition. It is also argued that, as a result of the fact the Channel Islands witnessed a very different trajectory of change from that seen in Britain and Ireland c.5000–3500 bc, this small group of islands has a great deal to tell us about the arrival of the Neolithic more widely.